1997
DOI: 10.1136/hrt.78.6.608
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin gene abnormalities in two patients with idiopathic dilated cardiomyopathy

Abstract: Two new cases of dilated cardiomyopathy (DC) caused by dystrophinopathy are reported. One patient, a 24 year old man, had a family history of X linked DC, while the other, a 52 year old man, had sporadic disease. Each had abnormal dystrophin immunostaining in muscle or cardiac biopsy specimens, but neither had muscle weakness. Serum creatine kinase activity was raised only in the patient with familial disease. Analysis of dystrophin gene mutations showed a deletion of exons 48-49 in the patient with familial D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 30 publications
2
48
0
1
Order By: Relevance
“…Mutations identified in the present study would be categorized as Group B, and all of the present patients had a deletion of exon 48. Muntoni et al 33 and Melacini et al 34 reported that exon 49 was important for cardiac function, and it has also been proposed that intron 48 may contain sequences important to cardiac muscle function. 33 From these findings, we hypothesize that the regions including exons 48 and 49 and intron 48 may be necessary for maintaining cardiac function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations identified in the present study would be categorized as Group B, and all of the present patients had a deletion of exon 48. Muntoni et al 33 and Melacini et al 34 reported that exon 49 was important for cardiac function, and it has also been proposed that intron 48 may contain sequences important to cardiac muscle function. 33 From these findings, we hypothesize that the regions including exons 48 and 49 and intron 48 may be necessary for maintaining cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…Muntoni et al 33 and Melacini et al 34 reported that exon 49 was important for cardiac function, and it has also been proposed that intron 48 may contain sequences important to cardiac muscle function. 33 From these findings, we hypothesize that the regions including exons 48 and 49 and intron 48 may be necessary for maintaining cardiac function. In addition, less severe mutations of dystrophin, such as missense mutations, may be associated with the sporadic form of DCM.…”
Section: Discussionmentioning
confidence: 99%
“…DMD and BMD mutations differentially affect the DMD gene: in DMD the mutations disrupt the reading frame, while mutations that cause BMD maintain the ORF (31,32) leading to the production of an internally deleted dystrophin protein. The size of the deletion does not correlate with the severity of the disease, as long as the reading frame rule is maintained (33)(34)(35)(36)(37)(38)(39)(40), and provided crucial domains of dystrophin such as the β-dystroglycan binding site are not removed by the deletion. While the central and distal rod domain is less vital for function (35), (some patients missing these domains only have very mild disease manifestations such as myalgia and muscle cramps, and mild weakness), in frame deletions that affect the binding of dystrophin to other proteins such as cytoskeletal actin or β-dystroglycan result in a severe phenotype (41,42).…”
Section: Becker Muscular Dystrophymentioning
confidence: 99%
“…Inheritance is linked to the X chromosome and can be dominant or recessive 51 . Sporadic cases are reported 50 . Prevalence of disorders involving dystrophin in DCM patients is still unknown.…”
Section: Genetic Factors and Familiar Formsmentioning
confidence: 99%
“…Anomalies affecting the gene codifying this substance cause Duchenne's dystrophy and Becker type muscular dystrophy. In rare cases, mutations involving this gene produce myocytolysis and cardiomyopathy development 50 . In males, the disease develops during adolescence and evolves quickly, but in females it develops later and with a slow progression.…”
Section: Genetic Factors and Familiar Formsmentioning
confidence: 99%